Strain distribution due to surface domains: a self-consistent approach with respect to surface elasticity - Fuhr, Javier; Müller, Pierre (Beilstein Journal of Nanotechnology, 2015)
Elastically mediated interactions between surface domains are classically described in terms of point forces. Such point forces lead to local strain divergences that are usually avoided by introducing a poorly defined cut-off length. In this work, we develop a self-consistent approach in which the strain field induced by the surface domains is expressed as the solution of an integral equation that contains surface elastic constants, Sij. For surfaces with positive Sij the new approach avoids the introduction of a cut-off length. The classical and the new approaches are compared in case of 1-D periodic ribbons.
Keywords: surface strain; surface elasticity; strain field

(untitled) - Mindlin, R. D. (J. Appl. Phys., 1936)

Theory of elasticity - Landau, L.; Lifshitz, E. (Pergamon Press, 1970)

(untitled) - Maradudin, A. A.; Wallis, R. F. (Surf. Sci., 1980)

(untitled) - Marchenko, V. I. (J. Exp. Theor. Phys., 1981)

(untitled) - Marchenko, V. I. (J. Exp. Theor. Phys., 1981)

(untitled) - Alerhand, O. L.; Vanderbilt, D.; Meade, R. D.; Joannopoulos, J. D. (Phys. Rev. Lett., 1988)

(untitled) - Hu, S. M. (J. Appl. Phys., 1979)

(untitled) - Hu, S. M. (Appl. Phys. Lett., 1978)

(untitled) - Müller, P.; Saúl, A. (Surf. Sci. Rep., 2004)

(untitled) - Kern, R.; Müller, P. (Surf. Sci., 1997)

(untitled) - Shenoy, V. B. (Phys. Rev. B, 2005)

Mechanical Stress on the Nanoscale - Müller, P. (Fundamentals of Stress and Strain at the Nanoscale Level: Toward Nanoelasticity, 2011)

(untitled) - Kern, K.; Niehus, H.; Schatz, A.; Zeppenfeld, P.; Goerge, J.; Comsa, G. (Phys. Rev. Lett., 1991)

(untitled) - Nozières, P.; Wolf, D. E. (Z. Phys. B: Condens. Matter, 1988)